2016
DOI: 10.1002/chin.201633238
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Pyrans: Heterocycles of Chemical and Biological Interest

Abstract: Pyrans: Heterocycles of Chemical and Biological Interest -[up to date information about the developments, exploration of new methodologies and varied biological activities of pyran analogs; 54 refs.]. -(KUMAR, K. A.; RENUKA, N.; KUMAR, G. V.; LOKESHWARI, D. M.; J. Chem. Pharm. Res. 7 (2015) 11, 693-700 ; Dep. Chem., Yuvaraja Coll., Univ. Mysore, Mysore 570 005, India; Eng.) -Koehler 33-238

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Six-membered heterocycles such as pyrans were considered as versatile substrates in the field of bioorganic chemistry [5,6]. Fused pyran derivatives represent an important class of compounds which possess high activity profile due to their wide range of biological activities [7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Six-membered heterocycles such as pyrans were considered as versatile substrates in the field of bioorganic chemistry [5,6]. Fused pyran derivatives represent an important class of compounds which possess high activity profile due to their wide range of biological activities [7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Как известно из литературы, замещенные пираны проявляют противоопухолевое, антибактериальное, противовоспалительное действие, противоотечные, спазмолитические, противогрибковые и противовоспалительные свойства [4][5][6][7][8][9][10][11]. ***…”
Section: R = 4-n(ch 3 ) 2 2-och 3 3-och 3 R 1 = Ch 3 4-c 2 H 5 unclassified
“…Pyran is also one of the important structural subunits found widely in natural products, e.g. coumarins, benzopyrans, sugars, flavonoids, xanthones, etc [15][16][17]. There are also some publications have reported that the combination of isatin and pyran nucleus could be a worthy choice for anticancer activity against various human tumor cell lines [18][19][20].…”
Section: Introductionmentioning
confidence: 99%